IMPLEMENTASI METODE DELPHI TERHADAP TUGAS AKHIR MATAKULIAH TEFL - Rima Ulfa; Eva Nurul Candra; Henny Suharyati (STKIP Subang, 2024)
In the era of globalization and rapid technological development. To prepare students to face social changes, the world of work and rapid technological advances, student competencies must be improved and prepared to face the demands of the times. and these optimal and relevant skills must be considered in the Teaching English as a Foreign Language (TEFL) course. Microteaching in TEFL courses must be adapted to the demands of the times. Therefore, the Delphi Method can be used to form guidelines and predict trends. The five main uses of Delphi in higher education, include: cost effectiveness, cost-benefit analysis, curriculum and campus planning, university education goals and objectives, generalized futuristic education goals and objectives. This research uses a descriptive qualitative method with a literature study approach. Keywords in qualitative research, namely, the process of understanding, and humans. both natural phenomena and man-made phenomena. These phenomena can be activities, and the difference between one phenomenon and another. This is indicated by the results of the standard deviation which has reached the optimal level. Based on the results of the priority sequence reference, it can be determined that students are required to record microteaching practices. themselves, and upload it to YouTube and then report it to the lecturer. YouTube's selection policy is based on this platform not limiting the length of the video, so students can be as creative as possible in class.